Planning and technology in developing nations - Joshi, Navin Chandra (Delhi UDH Publishing House, 1990)
; Regional planning-Developing countries; ; Population-Developing countries; -Developing countries
Keywords: Third world countries -- Economic development -- Population -- Developing countries -- Economic policy -- Technology; Underdeveloped countries -- Economic Conditions; Inflation (Finance) -- Developing countries